Acute hindlimb lameness in a 6-month-old cat. Issue 5 (May 2019) - Nappier, Michael; Robertson, Brooke; LeRoith, Tanya
Clinical presentation: A 6-month-old female spayed domestic shorthair cat was presented for investigation of acute right hindlimb lameness and paresis. What is your diagnosis?: Readers are encouraged to review the case history and consider what their diagnostic suspicion is. Also what is the preferred treatment for this injury? And what is the primary cause of this injury?